Prognostic value of activin A level in patients with advanced lung cancer and sarcopenia - V. V. Kechedzhyiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2024)
The aim of this work is to determine the prognostic role of activin A in patients with advanced lung cancer and sarcopenia.